Pengembangan Media Pembelajaran Berbasis Video Animasi Untuk Meningkatkan Pemahaman Konsep IPA Siswa Kelas V Sekolah Dasar - Wibowo, Salsabila Putri; Dahlan, Zaini (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to improve the understanding of fifth-grade elementary school students regarding the concepts of Science, particularly in relation to magnetism, electricity, and technology for life, through the development of animation-based video learning media. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data were collected through pre-tests and post-tests, expert validation, questionnaires, interviews, and observations. The developed media were validated by material experts, media experts, and design experts, and their practicality was assessed based on feedback from teachers and students. The validation results indicated a very high level of feasibility, with scores of 95% from material experts, 92% from media experts, and 93% from design experts. Practicality assessments obtained scores of 92% from students and 100% from teachers, categorizing the media as highly practical. Effectiveness testing showed a significant improvement in students’ conceptual knowledge, with an N-Gain score (g > 0.7) classified in the high category. Furthermore, N-Gain scores above 76 were interpreted as effective, with an average improvement in students’ understanding reaching 78.44%. These findings demonstrate that the developed animation video content can enhance conceptual understanding, increase students’ learning interest, and is relevant for use in abstract science materials such as magnetism and electricity. With high feasibility, practicality, and effectiveness levels, this learning media is suitable for use in classrooms as a teaching aid in science subjects at the elementary school level to improve student learning outcomes.